Mengukur Loyalitas Pelanggan Melalui Citra Toko dan Kepercayaan Pelanggan di Toko Retail - Prabowo, Hartiwi; viona, Viona (Bina Nusantara University, 2010)
An automobile spare parts shop at first having its sales increased. But, in 2008 the store experienced a significant decline in sales, so that the purpose of this study was to determine how much influence store image and customer trust on customer loyalty. This type of research is associative descriptive research. Data collection is conducted using questionnaires using Likert scales to 100 shop. Technical analysis is conducted using several techniques, which are Test Validity, Test Reliability, Test Normality, and Path Analysis. Results show that customer loyalty is influenced by greater consumer confidence than the image of the store. Therefore, PT Sloka Kencana Abadi must continue to improve the image of his shop by looking for a more strategic location making it easier to attract new customers, set prices according to the quality of the product and prices set by the competitor, maintain the quality of the product in the sense that the product is durable and free from damage, providing many choice of products making it easier for consumers to find the required product, and maintain these.Â